A critical review of geopolymer properties for structural fire-resistance applications. (10th October 2019) - Lahoti, Mukund; Tan, Kang Hai; Yang, En-Hua
Highlights: Geopolymers are chemically stable. Thermal deformations occurring in geopolymers. Strength of geopolymers is affected by microstructural and phase composition changes. Geopolymers show inherently superior fire resistance. Geopolymers require careful mix design to achieve superior fire resistance. Abstract: Protection of structures from fire is of extreme importance. Geopolymer is a novel material that has wide-ranging applications, and this review article focuses on assessing the potential of geopolymers towards enhancing the structural fire resistance by critically reviewing its properties subjected to elevated temperature exposure. The properties of geopolymers are categorized into three scales, namely, micro-scale, meso-scale and macro-scale, and are discussed at length. It is noted that geopolymers are chemically stable and do not undergo breakdown of chemical structure in contrary to OPC hydration products. Thermal deformations occurring in geopolymers, which cause macro-cracking, are discussed. Compressive strength of geopolymers is observed to be affected by microstructural changes (including crack formation, pore structure changes, densification, sintering, and melting) and phase composition changes (such as growth or destruction of crystals and transformations in geopolymer paste). Geopolymer-based binders show inherently superior fire resistance as compared to Portland cement-based binders. However, it requires careful mix design, to achieve substantial chemical stability, low volume changes, strength endurance, and spalling resistance. Factors such as choice of precursor, use of aggregates, total alkali content in geopolymer, water content, etc. are critical and should be controlled. The influence of these factors is discussed at length in this article. The current applications of geopolymers for heat and fire resistance have also been briefly presented.